2015
DOI: 10.1590/0103-64402013x0252
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Apical and Cervical Curvature Radius of Human Molars

Abstract: <p>To determine the frequency of apical and cervical curvatures in human molars using the radius method and cone-beam computed tomography (CBCT) images. Four hundred images of mandibular and maxillary first and second molars were selected from a database of CBCT exams. The radius of curvature of curved root canals was measured using a circumcenter based on three mathematical points. Radii were classified according to the following scores: 0 - straight line; 1 - large radius (r>8 mm, mild curvature); 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
0
21
0
2
Order By: Relevance
“…, Estrela et al . ). Moreover, previous studies have shown that small instruments are prone to distortion in clinical or simulated use as a result of stresses on the relatively small cross section leading to torsional failure (Sattapan et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Estrela et al . ). Moreover, previous studies have shown that small instruments are prone to distortion in clinical or simulated use as a result of stresses on the relatively small cross section leading to torsional failure (Sattapan et al .…”
Section: Discussionmentioning
confidence: 97%
“…Prior identification of the radius of curvature of a root canal constitutes a functional conduct (97). The most root canals of maxillary and mandibular first and second molars have some degree of curvature in the apical and cervical thirds, regardless the analyzed plane (98).…”
Section: Root Canal Preparationmentioning
confidence: 99%
“…The anatomic structures of human teeth (number of roots, root canals, apical foramina, root canal isthmuses, root ramifications, root curvatures, developmental disturbances), which constitute its micromorphology have been evaluated by destructive and non-destructive methodologies (1-7). Among the methods described in the literature include decalcification, radiography, vertical and cross-sectional cutting, histological evaluation, stereomicroscopy analysis, surgical microscopy, plastic casts, scanning electronic microscopy, cone beam computed tomography (CBCT) and micro-computed tomography (MCT) (2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%